A feasibility study on FrooTazz!! Sports Drink - Agbay, Arnel R. (College of Engineering, 2001)
A five-part study is conducted to determine the feasibility of a mango-flavored FrooTazz!! sports drink, a fluid replacement beverage with more mineral additives and no caffeine. The Market study part shows that the target market for FrooTazz!! sports drink is the NCR population segment agd 15 to 39, with annual income not less than Php 150,000. The market competitor analysis yields the following demand, market share and Sales plan for FrooTazz!! In the technical study, the production process is presented. The process consists of five stages: treatment of process water, heating of process water, preliminary mixing, final mixing, and packaging. A total of 14 workers are needed per batch. One batch takes about 75 minutes and there could be a maximum of 4 batches per day. The maximum output is pegged at 3250 400-mL bottles per batch. The plant site will be a 2,364 square meter lot inside the First Bulacan Industrial Zone in San Pablo, Malolos, Bulacan. In the Financial Study, the group computed an initialization cost of Php 33,000,000. 40% of this will be loaned from Metro Bank while the rest will be financed through owner's equity. the payback is calculated to be 0.55 years. The organization and management study indicates that a corporation is the best form of ownership for the company. Relevant features considered are: business life stability, transferability of shares, capital pooling, and attraction for loan financing. The social profitability study, several benefits to the society are identified, the most important of which are: (1) the project generates employment and income; (2) it benefits the consumers through price savings; (3) it increases revenues of related industries like its suppliers; (4) it generates national and local government income; (5) the group considered the environmental impacts of the project and made sure that its production will not cost any kind of pollution. From the five parts mentioned above, the study proponents conclude that the project is feasible and, therefore, is worth undertaking.